2016
DOI: 10.1007/5584_2016_37
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Stress as a Risk for Hypertension in Sub-Saharan Africans: Are We Ignoring the Odds?

Abstract: Globally most interventions focus on improving lifestyle habits and treatment regimens to combat hypertension as a non-communicable disease (NCD). However, despite these interventions and improved medical treatments, blood pressure (BP) values are still on the rise and poorly controlled in sub-Saharan Africa (SSA). Other factors contributing to hypertension prevalence, such as chronic emotional stress, might provide some insight for future health policy approaches.Currently, Hypertension Society guidelines do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…35 When corporal punishment was abolished in all South African schools, the impact on teachers' morale included loss of control, which may also support the increase in avoidance coping in this teachers' cohort. 4,13,36 Current findings also reflected psychological and cardiovascular vulnerability in the cohort of white teachers, who used consistent spiritual-centred, social support and DefS coping to combat stress.…”
Section: High-risk Cardiovascular Profile Among Urbandwelling White Tmentioning
confidence: 63%
See 2 more Smart Citations
“…35 When corporal punishment was abolished in all South African schools, the impact on teachers' morale included loss of control, which may also support the increase in avoidance coping in this teachers' cohort. 4,13,36 Current findings also reflected psychological and cardiovascular vulnerability in the cohort of white teachers, who used consistent spiritual-centred, social support and DefS coping to combat stress.…”
Section: High-risk Cardiovascular Profile Among Urbandwelling White Tmentioning
confidence: 63%
“…29 In our study, chronic stress in blacks was observed and is supported by other studies. 4,13 If combined with chronic higher alcohol consumption, circulatory disturbances such as vasospasms or ischaemic heart disease may ensue. [30][31][32][33][34] Indeed, recent findings in the SABPA cohort showed that habitual utilisation of DefS was often accompanied by alcohol abuse and a profile of reduced coronary perfusion.…”
Section: High-risk Cardiovascular Profile Among Urbandwelling Blacksmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is needed to tease out the distinctive features that predispose people of Bamileke descent to higher BP values and burden of hypertension irrespective of geographic location in Cameroon [42,49,51] and probably in other countries in the world. Such research should be designed to assess epidemiological, genetic, socioeconomic, cultural, behavioral, lifestyle and environmental factors affecting BP levels, hypertension awareness and treatment [83], individual responses to pharmacological therapy [84], emotional stress in sub-Saharan Africans [85] and gene-environment interactions [86].…”
Section: Discussionmentioning
confidence: 99%
“…While we could not find any significant relationship between any of the observed stress categories and blood pressure, others [ 36 ] observed a statistically significant relationship between blood pressure and women with premenstrual syndrome. A recent study has also observed that emotional stress is often ignored as a cause of high blood pressure in SSA [ 37 ]. In a behavioural study of under- and postgraduates in 208 Lagos students (equally split male : female, mean age 20.2), Agbu [ 38 ] found that the female students were more motivated and felt under greater pressure to get things done and find a job.…”
Section: Discussionmentioning
confidence: 99%